2000
DOI: 10.1088/0264-9381/17/5/316
|View full text |Cite
|
Sign up to set email alerts
|

Holography and the future tube

Abstract: The Future Tube T

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The symplectic structure of timelike geodesics in AdS 3 has been considered in [50] and the relevant coadjoint orbits and their quantization have been discussed in many references including [26]. Here, we provide a summary and make an explicit connection between the two.…”
Section: A Timelike Geodesicsmentioning
confidence: 99%
“…The symplectic structure of timelike geodesics in AdS 3 has been considered in [50] and the relevant coadjoint orbits and their quantization have been discussed in many references including [26]. Here, we provide a summary and make an explicit connection between the two.…”
Section: A Timelike Geodesicsmentioning
confidence: 99%
“…Its Shilov boundary Shilov (D 4 ) = Q 4 has precisely the same topology as the 4D conformally compactified real Minkowski space-time Q 4 ϭ M 4 ϭ ͑S 3 × S 1 ͒/Z 2 ϭ S 3 × RP 1 . For more details about Shilov boundaries, the conformal group, future tubes, and holography we refer to the article by Gibbons [2,70,74].…”
Section: Evaluation Of the Coupling Constantsmentioning
confidence: 99%
“…A study of Shilov boundaries, holography, and the future tube can be found in ref. 74. Furthermore, to resolve the scaling problems of Wyler's expression raised by Robertson, Gilmore showed why it is essential to use dimensionless volumes by setting the throat sizes of the anti-de Sitter hyperboloids to r = 1, because this is the only choice for r where all elements in the bounded domains are also coset representatives, and therefore, amount to honest group operations.…”
Section: ϫ2mentioning
confidence: 99%
“…[P ],m = m(|P | − 1) − P 2 /4. 19 The detailed fusion rules between generic massive representations are complicated, although bound to be of the form (3.59), given the validity of composition and distribution rules in (3.41) and (3.42). thus describe singletons for |P | = 1, and massless as well as massive ground states with minimal conformal weight for |P | > 1.…”
Section: On Massive Sector and Realization Of Spectral Flowmentioning
confidence: 99%
“…The model nonetheless contains non-unitary and non-topological states. Drawing on the continuum limit of discretized branes [15] as well as on the sigmamodel description of null surfaces in anti-de Sitter spacetime [17] (see also [18,19]), it makes sense to entertain the idea that the coset model based on…”
Section: Introductionmentioning
confidence: 99%